Environmental and operational performance is not always achieved when combined with cleaner production and lean production: An overview for emerging economies - Oliveira, José Augusto de [UNESP]; Devós Ganga, Gilberto Miller; Godinho Filho, Moacir; Silva, Diogo Aparecido Lopes; dos Santos, Mirian Paula [UNESP]; Aldaya Garde, Ivan Aritz [UNESP]; Penchel, Rafael Abrantes [UNESP]; Esposto, Kleber Francisco; Ometto, Aldo Roberto (Taylor & Francis, 2021)
The effect of combined Lean Production (LP) and Cleaner Production (CP) on Environmental and Operational Performance in emerging economies’ industries has not yet been studied. To address this gap, this work explores the effect of LP and CP practices on Environmental and Operational performance. A sample of 208 Brazilian organizations provided a set of results to test the four hypotheses: H1: LP practices are positively associated with CP practices in emerging economies’ industries; H2: Environmental performance is positively associated with operational performance in emerging economies’ industries; H3: LP practices are positively associated with environmental performance in emerging economies’ industries; H4: CP practices are positively associated with operational performance in emerging economies’ industries. H1 was confirmed and another three hypotheses were refuted, thus contributing to advancing the scientific literature dealing with CP and LP constructs with a comparative approach to Environmental and Operational performance in emerging economies’ industries.
Keywords: cleaner production; environmental performance; integration; Lean production; operational performance